2016
DOI: 10.1083/jcb.201611079
|View full text |Cite
|
Sign up to set email alerts
|

A dividing matter: Drp1/Dnm1-independent mitophagy

Abstract: Martin Graef highlights Yamashita et al.’s finding that mitophagy can occur independently of the canonical mitochondrial fission apparatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Although Drp1 has been reported to be required for mammalian mitophagy, there is mixed evidence on this issue ( Graef, 2016 ). To assess whether mitochondrial fission is required for ΔOTC clearance, we overexpressed a dominant-negative mutant of Drp1 in the ΔOTC-inducible cell line and found that Drp1K38A expression did not inhibit ΔOTC clearance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although Drp1 has been reported to be required for mammalian mitophagy, there is mixed evidence on this issue ( Graef, 2016 ). To assess whether mitochondrial fission is required for ΔOTC clearance, we overexpressed a dominant-negative mutant of Drp1 in the ΔOTC-inducible cell line and found that Drp1K38A expression did not inhibit ΔOTC clearance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Whether mitophagy requires prior Drp1-mediated mitochondrial fragmentation is still controversial. 62 For instance, mitochondrial division during mitophagy can occur in a Drp1-independent manner. 63 On the other hand, Drp1-dependent mitochondrial fragmentation might facilitate mitophagy by creating small-size fragments facilitating autophagosomal uptake.…”
Section: Discussionmentioning
confidence: 99%
“…63 On the other hand, Drp1-dependent mitochondrial fragmentation might facilitate mitophagy by creating small-size fragments facilitating autophagosomal uptake. 62 …”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence that fission regulates mitophagy 10 , 15 , the concept that Drp1 plays a direct mechanistic role in regulating mitophagy is controversial 71 . Evidence obtained in yeast 72 and mammalian cells 10 suggest that Drp1 (and Dnm1, the yeast homolog) is required for mitophagy while, in contrast, others have reported that Drp1 KO had no effect on mitophagy 73 or hypoxia-induced upregulation of mitophagy 74 , but may protect mitochondria from PINK/Parkin-mediated “wholesale mitophagy” 11 .…”
Section: Discussionmentioning
confidence: 99%